PHYSICAL ACTIVITY AND EARLY CHILDHOOD EDUCATION: TOWARDS A CRITICAL SPORTS PEDAGOGY - Emanuele ISIDORI; Alessandra FAZIO; Elsa Maria BRUNI (Cluj University Press, 2018)
So-called "Bolonia Process" has reformed national education systems in Europe and introduced the figure of a general teacher in primary schools and kindergartens. This has also happened in Italy, where early childhood educators and primary teachers are trained in University departments of Educational Sciences to become general educators and teachers in both Kindergartens and primary schools without any specific training, for example, in physical/ sports education. This lack in the preparation of kindergarten educators and primary school teachers is causing a decrease of interest for the teaching of physical activity and sports education by kindergartens educators. Usually, an educator who has scarce or not-enough developed competencies in a specific subject matter of the curriculum does not like to be involved in such a kind of activities. The consequences of this can be seen in the reduction of the level of physical and motor competencies and skills in the children attending kindergartens. Starting from this genesis, the primary aim of this paper is to reflect upon the consequences of the new reform of European educational systems on the teaching of physical activity in the kindergarten and early childhood, and upon the educational challenges they imply for teachers. In conclusion, will show the key role that the general teacher with specific competencies and skills in physical and sports education can play, along with family, to foster physical and sports education in early childhood and sketch a possible model for teaching it.